An Advanced Adaptive Mesh for Beam-Column Finite Elements on Transient Dynamic Analysis - Martinez, Edgar David Mora; Khaji, Naser (Salehan Institute of Higher Education, 2024)
This research examines the influence of truncation error reduction on the nonlinear dynamic analysis of complex framed structures. A modified -adaptive method, incorporating inertial and damping forces in addition to the common restitutive forces, is introduced to refine the mesh and enhance accuracy. To address convergence challenges arising from increased complexity, Ritz modal shapes are utilized to reconstruct the mass matrix, excluding detrimental modes. The proposed formulation is validated through rigorous computational models and experimental data. Six building case studies, varying in complexity, were analyzed using the modified -adaptive method. The results revealed substantial variations in frequency and displacement responses, ranging from 6% to 50% and 0.8% to 63%, respectively. These disparities underscore the significant influence of nonlinear behavior on structures with high-order shape functions. The proposed formulation is theoretically more accurate. Therefore, the findings emphasize the necessity of employing mesh refinement techniques to obtain accurate nonlinear dynamic analysis results, particularly for complex structures with pronounced nonlinear characteristics. This study contains the background of a software called MainModelingStr. Doi: 10.28991/CEJ-2024-010-12-01 Full Text: PDF